Fostering Student Engagement in the English Class Through Game Choice (2023)
ABSTRACT: This study was an action research project designed to attempt to enhance students’ engagement in the English class through game choice. It was developed during two school terms. The participants were 20 eighth graders at Institución Educativa Francisco Luis Hernández Betancur of Medellín. Most of them were approximately from thirteen to fifteen years old. Data collection instruments included a pre and post-test, observations and a rubric, students journal, a focus group interview, and a survey. Data was analyzed using the triangulation method with all the sources. The results of the project showed that giving students game choice in the classroom increases students’ engagement in the cognitive, behavioral, and emotional dimension, while for the social dimension the effect of the intervention was not as significant.